The role of mineral fertilizers in transforming Philippine agriculture - Briones, Roehlano M. (International Food Policy Research Institute, 2014)
The Philippines is an island nation, comprised of 7,107 islands that are split into 3 geographical divisions: Luzon, Visayas, and Mindanao. In 2013, agriculture contributed 10.45 percent to GDP (PSA-NSCB, 2014) and 31 percent to employment (PSA-BLES, 2014). More im-portantly, its contribution to national and household food security is significant. Cereal production increased from 7.6 million tons in 1970 to 22.1 million tons in 2010. During the same period, fertilizer use increased from 201,000 nutrient tons to 771,000 nutrient tons (FAOSTAT). In promoting cereal production, especially rice production, increased fertilizer use, along with improved seeds and other agronomic practices, played a key role.